Listeria Rhombencephalitis Complicating Anti-TNF Treatment during an Acute Flare of Crohn’s Colitis - L. Stratton; G. R. Caddy (Case Reports in Gastrointestinal Medicine)
Patients with Crohn’s disease often require the use of immunosuppressant drugs to control disease activity. Such medication includes steroids, azathioprine, and biologic therapy. These suppress the immune response, and the patient is more susceptible to infection. We present a case of a 69-year-old gentleman with a history of Crohn’s colitis who had ongoing symptoms of diarrhoea in spite of standard treatment. Biologic therapy was considered to be the next step, and screening for infection was undertaken prior to use. Three days following anti-TNF treatment, he became drowsy, and examination revealed pyrexia, slurred speech, and nystagmus. Investigation revealed presence of Listeria rhombencephalitis. He demonstrated poor neurological recovery. Listeria monocytogenes is an infection commonly associated with food sources. Some patients develop a self-limiting diarrhoeal illness, but in the immunosuppressed population, the clinical features may be more sinister. Cotrimoxazole prophylaxis is already recommended for those on triple immunosuppression. We propose the early initiation of this treatment, including where biologic use is anticipated. In those on multiple immunosuppressants, a diet similar to that followed in pregnancy may minimise risk of acquiring this infection. Clinicians must always have a high index of suspicion for opportunistic infection in such immunocompromised patients.